2020
DOI: 10.1002/chem.201904845
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Characterization of Nickel‐Functionalized Covalent Organic Framework NiCl@RIO‐12 for Heterogeneous Suzuki–Miyaura Catalysis

Abstract: As eries of nickel-decorated covalento rganic frameworks, NiCl@RIO-12, were prepared using the post-synthetic modification strategy,t hat is, by reactingN iCl 2 with pristine RIO-12 under alkaline conditions. Interestingly,t hey retained their crystallinity andt he amount of nickel incorporated could be tuned from 3.6 to 25 wt %a ccording to the reaction conditions. The incorporation of ah igher amount of nickel in NiCl@RIO-12 consistently led to al ower Brunauer-Emmett-Teller surfacea rea. Additionally,n oa g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 77 publications
(153 reference statements)
1
23
0
Order By: Relevance
“…Another possibility is that the relatively weak diffraction signals from the framework are attenuated by the presence of species with higher scattering factor (chlorine) randomly oriented within the pore structure, which dominates the scattering. This was observed in similar cases, where the framework is indeed crystalline, but its corresponding diffraction signals are suppressed by the heavier species confined in their pores [23–25] …”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Another possibility is that the relatively weak diffraction signals from the framework are attenuated by the presence of species with higher scattering factor (chlorine) randomly oriented within the pore structure, which dominates the scattering. This was observed in similar cases, where the framework is indeed crystalline, but its corresponding diffraction signals are suppressed by the heavier species confined in their pores [23–25] …”
Section: Resultssupporting
confidence: 58%
“…This was observed in similar cases, where the framework is indeed crystalline, but its corresponding diffraction signals are suppressed by the heavier species confined in their pores. [23][24][25] Pararosaniline hydrochloride can be in equilibrium between its ionized and neutral forms (Scheme 1), depending on the solvent. Its ionic form is favoredi np olar protic solvents.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, since this probable Guinier shoulder is only notable for RIO-12 in the SAXS range, it suggests that RIO-12's grain is smaller than the other microporous materials' grains. Additionally, while investigating a sample of RIO-12 containing 3.6 wt% of nickel in our group's recent study (Maia et al, 2020), high-resolution transmission electron microscopy (HRTEM) showed a compelling result. The micrograph of the modified material ( Fig.…”
Section: Figurementioning
confidence: 97%
“…In addition, Zhang research group established a Cu@PI‐COF heterogeneous catalyst, which was highly stable and can be recycled 8 times in Chan‐Lam coupling reaction of aryl borate without loss of the high catalytic activity [26] . Renata et al [27] also developed a Ni‐doped RIO‐12 COF hybrid for organic coupling reactions and the hydroxyl groups of α‐imine‐phenol in the RIO‐12 COF can coordinate with Ni ion to form a catalytically active Ni‐COF complex.…”
Section: Introductionmentioning
confidence: 99%